Reading the silver screen : a film lover's guide to decoding the art form that moves - Foster, Thomas C. (Harper Perennial, 2016)
"No art form is as instantly and continuously gratifying as film. When the house lights go down and the lion roars, we settle in to be shocked, frightened, elated, moved, and thrilled. We expect magic. While we're being exhilarated and terrified, our minds are also processing data of all sorts--visual, linguistic, auditory, spatial--to collaborate in the construction of meaning. Thomas C. Foster's Reading the Silver Screen will show movie buffs, students of film, and even aspiring screenwriters and directors how to transition from merely being viewers to becoming accomplished readers of this great medium. Beginning with the grammar of film, Foster demonstrates how every art form has a grammar, a set of practices and if-then propositions that amount to rules. He goes on to explain how the language of film enables movies to communicate the purpose behind their stories and the messages they are striving to convey to audiences by following and occasionally breaking these rules. In Reading the Silver Screen, readers will gain the expertise and confidence to glean all they can from the movies they love,"--Amazon.com.